2020
DOI: 10.3390/microorganisms8020233
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Sediment DNA Sequencing Reveals Azo Dye Degrading Bacteria Inhabit Nearshore Sediments

Abstract: Estuaries and coastal environments are often regarded as a critical resource for the bioremediation of organic pollutants such as azo dyes due to their high abundance and diversity of extremophiles. Bioremediation through the activities of azoreductase, laccase, and other associated enzymes plays a critical role in the removal of azo dyes in built and natural environments. However, little is known about the biodegradation genes and azo dye degradation genes residing in sediments from coastal and estuarine envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…Azo dyes, such as Congo red, are highly toxic, carcinogenic, and mutagenic. They are hazardous to the respiratory system because of their vapor, and they are dangerous in cases of skin contact, eye contact, and swallowing [ 5 , 6 , 7 , 8 , 9 , 10 ]. During their degradation, carbon dioxide, nitrogen oxide, and sulfur oxides may form.…”
Section: Introductionmentioning
confidence: 99%
“…Azo dyes, such as Congo red, are highly toxic, carcinogenic, and mutagenic. They are hazardous to the respiratory system because of their vapor, and they are dangerous in cases of skin contact, eye contact, and swallowing [ 5 , 6 , 7 , 8 , 9 , 10 ]. During their degradation, carbon dioxide, nitrogen oxide, and sulfur oxides may form.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial cultures are favored over other microorganisms, mainly fungi, in the case of anthraquinone dye (Balasubramanian et al, 2011;Li et al, 2019) because bacteria can be grown fast, can survive in harsh conditions, and are easy to manipulate. A recent study identified azoreductase and naphthalene-degrading genes in bacteria found near seashore that decolorized naphthalene-based dyes (Zhuang et al, 2020). Therefore, bacteria can reduce the ecotoxicity of the azo dyes and decolorize the vast array of dyes like amaranth, naphthalene, and acidic and anthraquinone dyes.…”
Section: Bacterial Reductionmentioning
confidence: 99%
“…It was reported that Azure B dye had shown its toxicity in the biological cells by the intercalation between the DNA and the membrane lipid (Haq and Raj, 2018). Various toxic substances are present in the dyes, which have caused bleeding, nausea, and ulceration and have affected human health (Zhuang et al, 2020). Reactive dyes also cause various allergic reactions and toxicity to aquatic life if released in the water, and are mutagenic and carcinogenic toward humans (Das and Mishra, 2017).…”
Section: Cellular and Molecular Toxicitymentioning
confidence: 99%
“…Additionally, combined with the metatranscriptomic approach, it can be used to understand the significant role of the functional genes contributing to microbial communities for textile degradation during active metabolic processes. Also, systematic studies on the effect of azo dye gradients on azo dye-related degradation genes are required to assess the role of azo dyes on the proliferation and prevalence of azo dye-related degradation genes in environmental sites (Sho et al, 2004;Suenaga et al, 2009;Zhuang et al, 2020;Srinivasan and Sadasivam, 2021;Wang et al, 2021). Furthermore, in the continuum of the recent research studies and the context of the textile industry-based shotgun metagenomics approach, we have tried to address the functional potential of the microbial community structure dominant in the industrial wastewater, ETP, and CETP sites.…”
Section: Metabolic Pathways and Mechanism For The Biodegradation Of Azo Dyes In Textile Industry Effluentsmentioning
confidence: 99%